Analisis senjata kimia melalui uji profisiensi organisation prohibition of chemical weapon (OPCW) - Evita Boes; Dyah Styarini; Nuryatini Nuryatini; Harry Budiman (Badan Standardisasi Nasional, 2009)
Identification of some chemicals weapons in the water and organic sample has been carried out during 21th proficiency testing conducted by OPCW (Organisation Prohibition of Chemical Weapon). The samples were prepared and analysed in accordance with the principles describe in the work instructions for the preparation of test samples for OPCW proficiency test. The extract of samples were analysed and identified by GC-EI-MS, GCCI-MS, GC-FPD, GC-NPD and LC-MS. From 7 spiking chemical weapons introduced to water and organic sample, 3 spiking chemicals could be identified such as Bis(2,4,4 trimethylpentyl)methylphosphonate, 2-(N-Ethyl-N-isoprophylamino)etanol and Bis(2-diisoprophylaminoethyl)disulfide.